Writing a prescription: the law and good practice. (2nd November 2021) - Bowles, Alexandra
Abstract : Paramedic independent prescribing offers an opportunity to improve patient access to medications. However, incomplete, unclear or incorrectly written prescriptions can cause harm to patients. This article in the Prescribing Paramedic series considers: the legal requirements a prescription must meet for prescription-only medicines and controlled drugs; common errors that may occur during prescription writing and potential solutions; and best practice recommendations for prescribers to follow when writing a prescription to minimise errors. The advantages and disadvantages of electronic prescribing are discussed.